A new Pr0.25Nd0.25Sr0.5MnO3-δ cathode for proton-conducting solid oxide fuel cells. Issue 8 (15th April 2022) - He, Shoucheng; Yin, Yanru; Bi, Lei; Dai, Hailu
Abstract: Manganate cathodes have good stability, but their performance at intermediate temperatures is not satisfactory, restricting the application for proton-conducting solid oxide fuel cells (H–SOFCs). A new composition, Pr0.25 Nd0.25 Sr0 . 5 MnO3-δ (PNSM), is proposed to solve this problem. First-principles calculations indicate PNSM should have better performance than the classical Sr-doped LaMnO3 (LSM) cathode by favoring the formation of oxygen vacancies and proton defects. Experimental studies indicate that the PNSM material can be successfully synthesized and show good chemical stability. The H–SOFC using the single-phase PNSM cathode shows improved performance than that using the traditional LSM cathode, demonstrating the prediction from the theoretical calculations. Further optimizing the cell structure, an encouraging performance of 1266 mW cm −2 at 700 °C is obtained, which is larger than many other manganates cathode-based H–SOFCs. The performance is even comparable to many high-performing cathodes for H–SOFCs, indicating PNSM is an efficient cathode material for H–SOFCs.